New Malaysia, Brexit and US-China Trade War – Credit Risk to Malaysian Banks - Yong, Wooi Keong *; Yong, Wooi Meng (IntechOpen, 2020)
A country’s economic prosperity is intimately linked to the external and internal forces that exert influences on its economy. While some of these forces may not be under the overt control of the country’s economic planners, any disruption to the economy by these forces may just tip the balance that causes financial hardship to millions of people. Certainly, national governments through fiscal and monetary policy measures may attempt to prevent such a catastrophe, but what happens if at such a critical time, the needed government leadership is suddenly not available? In such a situation, what will be the most appropriate reaction from the central bank, and what is the likely effect to the country’s banking industry? While this scenario might sound like an interesting thought experiment in a banking classroom, a similar situation is in fact unfolding in real life at this very moment in Malaysia